Challenges and Considerations in Optimizing Ovarian Stimulation Protocols in Oncofertility Patients - Coyne, Kathryn; Purdy, MacKenzie; O’Leary, Kathleen; Yaklic, Jerome L.; Lindheim, Steven R.; Appiah, Leslie A. (Frontiers in Public Health, 2014)
The scope of cancer treatment in women of childbearing age has changed in the last decade. Fertility preservation is no longer an afterthought but central to multi-disciplinary cancer treatment planning and should be addressed due to the cytotoxic effects cancer therapy. However, oncology patients present as a unique treatment challenge as the physician must balance the urgency of fertility preservation with the risks of delaying cancer therapy. Controlled ovarian stimulation (COS) is routinely applied in assisted reproductive technology but can be contraindicated in women with estrogen-receptor positive tumors. This paper reviews some of the challenges to consider when using COS and newer stimulation protocols to minimize risks and optimize outcomes in oncofertility patients.